Pengaruh Pengetahuan Kewirausahaan dan Lingkungan Keluarga Terhadap Minat Berwirausaha Pada Siswa Kelas XII di SMK Negeri 1 Singaraja - Kadek Yuliani; Made Ary Meitriana (Universitas Pendidikan Ganesha, 2025)
This research was conducted with the aim of understanding (1) the effect of entrepreneurial knowledge on entrepreneurial interest among 12th-grade students at SMK Negeri 1 Singaraja. (2) The effect of family environment on entrepreneurial interest among 12th-grade students at SMK Negeri 1 Singaraja (3) the effect of entrepreneurial knowledge and family environment on entrepreneurial interest among 12th-grade students at SMK Negeri 1 Singaraja. The type of research used is causal quantitative research. The sampling technique employed is non-probability sampling, and the research sample consists of all students in the twelfth grade at SMK Negeri 1 Singaraja, totaling 137 samples. The data collection method used a questionnaire and was analyzed using multiple linear regression. The research results indicate that (1) there is a positive and significant influence of entrepreneurial knowledge on entrepreneurial interest, partially, with a significance value of 0.000 < 0.05. (2) There is a positive and significant influence of the family environment on entrepreneurial interest, partially, with a significance value of 0.000 < 0.05. (3) There is a positive and significant influence of entrepreneurial knowledge and the family environment on entrepreneurial interest simultaneously, with a significance value of 0.000 < 0.05.